English Medium Instruction in South Asia: Addressing Equity and Inclusion in Education - Khadka , Bishnu Kumar (AMC Multidisciplinary Research Journal, 2025)
English Medium Instruction (EMI) has become an increasingly prominent phenomenon across South Asia, driven by its perceived association with global competitiveness and socioeconomic mobility. This review-based paper offers a comprehensive overview of EMI in the region, analyzing its historical origins, evolving role in education systems, and the challenges and implications it poses for equity and social justice focusing particularly on its impact on educational access, social mobility, and linguistic diversity. The study explores how colonial legacies have shaped the status of English as the dominant language of instruction in countries like India, Pakistan, Bangladesh, Nepal, and Sri Lanka. It further investigates how these nations have adopted EMI to align with global educational trends, despite disparities in access and outcomes. Based on the review of existing literature, the findings highlight the challenges posed by inadequate teacher preparedness, resource constraints, and the potential marginalization of students from lower socioeconomic backgrounds. Drawing on empirical studies and policy analysis, the paper also discusses the effectiveness of EMI in enhancing academic performance, language proficiency, and employability, while acknowledging the risks of reinforcing educational inequalities. It also suggests potential strategies for addressing these challenges, advocating for a more balanced, context-sensitive approach to EMI implementation. By examining the multifaceted impact of EMI in South Asia, this review contributes to the ongoing debate on its role in shaping the future of education in linguistically diverse and economically stratified societies. It concludes by offering recommendations for creating equitable and linguistically sensitive EMI frameworks that accommodate the region’s diverse sociocultural contexts, ensuring that all students, regardless of background, benefit from English-medium education.